An evaluation of routing in vehicular networks using analytic hierarchy process. Issue 8 (2nd February 2015) - Katsaros, Konstantinos; Dianati, Mehrdad; Sun, Zhili; Tafazolli, Rahim
Abstract: This paper presents a comprehensive study of the performance of routing protocols in distributed vehicular networks. We propose a novel and efficient routing protocol, namely cross‐layer, weighted, position‐based routing, which considers link quality, mobility and utilisation of nodes in a cross layer manner to make effective position‐based forwarding decisions. An analytic hierarchy process approach is utilised to combine multiple decision criteria into a single weighting function and to perform a comparative evaluation of the effects of aforementioned criteria on forwarding decisions. Comprehensive simulations are performed in realistic representative urban scenarios with synthetic and real traffic. Insights on the effect of different communication and mobility parameters are obtained. The results demonstrate that the proposed protocol outperforms existing routing protocols for vehicular ad hoc networks, including European Telecommunications Standards Institute (ETSI's) proposed greedy routing protocol, greedy traffic aware routing protocol and advanced greedy forwarding in terms of combined packet delivery ratio, end‐to‐end delay and overhead. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : This paper presents a comprehensive study of the performance of routing protocols in distributed vehicular networks. We propose a novel and efficient routing protocol, namely, cross‐layer, weighted and position‐based routing, which considers link quality, mobility and utilisation of nodes in a cross layer manner to make effective position‐based forwarding decisions. An analytic hierarchy process approach is utilised to combine multiple decision criteria into a single weighting function and to perform a comparative evaluation of the effects of aforementioned criteria on forwarding decisions.